Enriching the academic wordlist and Secondary Vocabulary Lists with lexicogrammar: Toward a pattern grammar of academic vocabulary. (December 2019) - Green, Clarence
Abstract: The interaction between lexis and grammatical patterns has been known in the literature as lexicogrammar, and research in this area has suggested that learning vocabulary necessitates learning accompanying grammatical patterns. Existing academic wordlists, focusing on isolated vocabulary items out of grammatical context, thus could be enriched with their target vocabulary's common grammatical patterns. This paper therefore describes the lexicogrammar of academic vocabulary on the widely used Academic Word List and recently published Secondary Vocabulary Lists. From a corpus of secondary school reading material, it extracts the grammatical patterns frequently associated with academic vocabulary. Drawing on frameworks such as Pattern Grammar and Construction Grammar, and using methods such as colligation and collexeme analysis, this study describes the subset of academic vocabulary associated with particular grammatical patterns. Furthermore, the results of this study are developed into a pedagogical resource that lists the vocabulary and grammar interactions, along with authentic examples of the interaction from the corpus and relevant statistical information. The paper offers specific pedagogical uses of how the resource, named the Lexicogrammar of Academic Vocabulary lists (LAV lists), can be used for developing the breadth and depth of academic vocabulary knowledge in students. Highlights: Grammatical patterns are described for the Academic Word List and Secondary Vocabulary Colligation. A pedagogical resource is developed, the Lexicogrammar of Academic Vocabulary (LAV) Lists. Grammatical pattern analysis reveals the common context for the presentation of academic vocabulary. Pedagogical activities for developing the lexicogrammatical knowledge of academic vocabulary are described.